2005
DOI: 10.1038/nature03560
|View full text |Cite
|
Sign up to set email alerts
|

Palaeomagnetism of the Vredefort meteorite crater and implications for craters on Mars

Abstract: Magnetic surveys of the martian surface have revealed significantly lower magnetic field intensities over the gigantic impact craters Hellas and Argyre than over surrounding regions. The reduced fields are commonly attributed to pressure demagnetization caused by shock waves generated during meteorite impact, in the absence of a significant ambient magnetic field. Lower than average magnetic field intensities are also observed above the Vredefort meteorite crater in South Africa, yet here we show that the rock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
66
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 21 publications
6
66
0
1
Order By: Relevance
“…For example, magnetic fields can be generated during a shock event, providing a possible explanation for high magnetic remanence found in young lunar glasses (14). In addition, a recent study suggested that randomization of paleomagnetic records by impactgenerated fields may be responsible for the weak magnetic field intensity observed at the impact basins of Mars (15). As shown for pyrrhotite (16), impacts can demagnetize minerals, providing an alternative interpretation for the weak fields at the impact basins.…”
mentioning
confidence: 99%
“…For example, magnetic fields can be generated during a shock event, providing a possible explanation for high magnetic remanence found in young lunar glasses (14). In addition, a recent study suggested that randomization of paleomagnetic records by impactgenerated fields may be responsible for the weak magnetic field intensity observed at the impact basins of Mars (15). As shown for pyrrhotite (16), impacts can demagnetize minerals, providing an alternative interpretation for the weak fields at the impact basins.…”
mentioning
confidence: 99%
“…It may be reasonable due to much slower projectile velocity (only 0.8 km/s) in this study compared with much faster velocity (5.2 to 6.0 km/s) as Crawford and Schultz (1991) claimed the PIRM. Carporzen et al (2005) found strongly magnetized and randomly oriented directions changing over centimeter length scales at the Vredefort meteorite crater in South Africa. They attributed the unusual magnetization to PIRM.…”
Section: Discussionmentioning
confidence: 99%
“…The largest volcanic edifices (Tharsis, Elysium, Olympus) as well as the largest impact craters (Hellas, Argyre, Isidis) are devoid of significant magnetic field at satellite altitude, which is generally attributed to local demagnetization of an otherwise magnetized crust. Thermal demagnetization due to volcanoes (Langlais et al 2004) and impacts as well as impact excavations are likely explanations (Artemieva et al 2005;Carporzen et al 2005).…”
Section: Marsmentioning
confidence: 99%